Effect of parallel electric field on charged particle precipitation - Prasad R.; Singh R.N. (My University, 2025)
Considering the presence of electric field parallel to geomagnetic field in the magnetosphere, the problem of wave-particle interaction has been considered. Dispersion equation of whistler mode wave in presence of parallel electric field has been derived. Using the effective dispersion equation, the wave-particle interaction has been reformulated to account for the effect of parallel electric field. Using charged particle energy spectrum and magnetospheric field and plasma models, the flux of electron precipitation has been computed. It is shown that the parallel electric field plays an important role and may work in simultaneity with other processes known for enhancement of electron precipitation. © 1981.